2008
DOI: 10.1021/ja077797f
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Mediated Photoinduced Electron Transfer in a Pyridinium Ionic Liquid

Abstract: The dynamics of electron transfer reactions in butyl pyridinium bis(trifluoromethanesulfonyl)imide (BuPyr-NTf2) and other solvents have been explored using laser flash photolysis. In these experiments, benzophenone (BP), duroquinone (DQ), and 9-cyanoanthracene (9CA) were used as excited-state acceptors, 1,4-diazabicyclo[2.2.2]octane and hexamethylbenzene were used as ground-state donors, and methyl viologen (MV2+) was used as a probe molecule. Analysis of kinetic and spectroscopic data from these experiments s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 26 publications
3
32
0
1
Order By: Relevance
“…The higher rates in ILs may be realized in more organized media, such as IL crystals. A similar phenomenon was observed by photoinduced electron transfer in ionic liquids [18].…”
Section: Aqs+ Bpy • Aqssupporting
confidence: 81%
“…The higher rates in ILs may be realized in more organized media, such as IL crystals. A similar phenomenon was observed by photoinduced electron transfer in ionic liquids [18].…”
Section: Aqs+ Bpy • Aqssupporting
confidence: 81%
“…The PET reaction in acetonitrile medium was found to fall in the normal Marcus region. However, PET reaction rate in some pure ionic liquids was also found to fall in the normal Marcus region showing Rehm-Weller behavior[23,24]. But in this case the inherent heterogeneous behavior of the ionic liquid is responsible for getting such type of inversion which we have observed previously in various heterogeneous environment like micelle, reverse micelle, cyclodextrin, etc.…”
mentioning
confidence: 77%
“…We have already reported PET in an aliphatic ionic liquid DAF using the same donor acceptor pair and observed saturation in the electron transfer rate vs free energy correlation curve [22]. Falvey and co-worker have studied PET reaction in two room temperature ionic liquid and observed that the PET reaction rate follow the Rehm-Weller behavior [23] and they have also studied solvent mediated PET in a pyridinium ionic liquid [24]. Recently LyndenBell have investigated some simulation studies of model systems of two ionic liquids and compare with acetonitrile to judge the applicability of Marcus theory in ionic liquids [25,26].…”
Section: Introductionmentioning
confidence: 88%
“…The pyridinium ionic liquids have already been successfully applied in many processes. The example may be the photoinduced electron transfer (PET) [1] and conductive liquids in electrochemistry. The others, such as the accelerated amine-catalyzed Morita-Baylis-Hillman reactions [2], recyclable and highly efficient organocatalysts for the asymmetric Michael addition reactions [3], the tetrahydropyranylation of alcohols [4], the Friedel-Crafts alkylation reactions [5], the Diels-Alder reactions [6], Grignard reactions [7], or the Fischer esterification [8].…”
Section: Introductionmentioning
confidence: 99%